2013
DOI: 10.1093/mnras/stt530
|View full text |Cite
|
Sign up to set email alerts
|

Broad iron line in the fast spinning neutron-star system 4U 1636−53

Abstract: We analysed the X-ray spectra of six observations, simultaneously taken with XMMNewton and Rossi X-ray Timing Explorer (RXTE), of the neutron star low-mass X-ray binary 4U 1636-53. The observations cover several states of the source, and therefore a large range of inferred mass accretion rate. These six observations show a broad emission line in the spectrum at around 6.5 keV, likely due to iron. We fitted this line with a set of phenomenological models of a relativistically broadened line, plus a model that a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(122 citation statements)
references
References 61 publications
(142 reference statements)
10
111
1
Order By: Relevance
“…As previously reported by Sanna et al (2013) the soft state and the hard state of 4U 1636-53 (see Figure 2 in Sanna et al 2013). Our results are therefore consistent with the picture that frequency drifts of the mHz QPOs are only observed in the state transition.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…As previously reported by Sanna et al (2013) the soft state and the hard state of 4U 1636-53 (see Figure 2 in Sanna et al 2013). Our results are therefore consistent with the picture that frequency drifts of the mHz QPOs are only observed in the state transition.…”
Section: Discussionsupporting
confidence: 94%
“…We found that both a thermal and a Comptonised component were necessary to fit the continuum, whereas two thermal components plus a Comptonised component (e.g., Sanna et al 2013;Lyu et al 2014) was too complex a model given the quality of the data. For the thermal component either a blackbody or an accretiondisc model could fit the data well.…”
Section: Spectral Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The NS nature of the compact object has been confirmed through the detection of thermonuclear X-ray bursts (Hoffman et al 1977;Galloway et al 2006;Zhang et al 2011), which show asymptotic millisecond burst oscillations, indicating a spin frequency of ∼581 Hz (Zhang et al 1997;Giles et al 2002;Strohmayer & Markwardt 2002). In addition to variability studies, the X-ray energy spectra, which show broad, asymmetric Fe emission lines, have been investigated (Pandel et al 2008;Cackett et al 2010;Ng et al 2010;Sanna et al 2013). …”
Section: U 1636−53mentioning
confidence: 93%
“…The broad line of 4U 1705-44, with others lines detected with XMM-Newton, is also discussed in Ng et al (2010) who point out the potential role of the pileup in the broadening of the line. However, recent developments of the subject can be found in Di Salvo et al (2015), Cackett & Miller (2013), Sanna et al (2013), Egron et al (2013), Piraino et al (2012), Cackett et al (2012), andMiller et al (2010).…”
Section: Introductionmentioning
confidence: 99%